Menthol evokes Ca2+ signals and induces oxidative stress independently of the presence of TRPM8 (menthol) receptor in cancer cells - Mustafa NazÄ±roÄlu; Walter Blum; Katalin JÃ³svay; Bilal ÃiÄ; Thomas Henzi; ZoltÃ¡n OlÃ¡h; Csaba Vizler; Beat Schwaller; LÃ¡szlÃ³ Pecze (Redox Biology, 2018)
Menthol is a naturally occurring monoterpene alcohol possessing remarkable biological properties including antipruritic, analgesic, antiseptic, anti-inflammatory and cooling effects. Here, we examined the menthol-evoked Ca2+ signals in breast and prostate cancer cell lines. The effect of menthol (50â500Â ÂµM) was predicted to be mediated by the transient receptor potential ion channel melastatin subtype 8 (TRPM8). However, the intensity of menthol-evoked Ca2+ signals did not correlate with the expression levels of TRPM8 in breast and prostate cancer cells indicating a TRPM8-independent signaling pathway. Menthol-evoked Ca2+ signals were analyzed in detail in Du 145 prostate cancer cells, as well as in CRISPR/Cas9 TRPM8-knockout Du 145 cells. Menthol (500Â ÂµM) induced Ca2+ oscillations in both cell lines, thus independent of TRPM8, which were however dependent on the production of inositol trisphosphate. Results based on pharmacological tools point to an involvement of the purinergic pathway in menthol-evoked Ca2+ responses. Finally, menthol (50â500Â ÂµM) decreased cell viability and induced oxidative stress independently of the presence of TRPM8 channels, despite that temperature-evoked TRPM8-mediated inward currents were significantly decreased in TRPM8-knockout Du 145 cells compared to wild type Du 145 cells. Keywords: Ca2+ oscillations, TRPM8, Menthol, Oxidative stress, Purinergic signaling